Novel Risk Factors in Long-term Hypertension Incidence in Type 1 Diabetes Mellitus - Sahakyan, Karine (2010)
BACKGROUND: Data from longitudinal studies suggest that biomarkers of inflammation and endothelial dysfunction are associated with development of hypertension. None of these studies have examined the association of these markers with hypertension risk in persons with diabetes. We examined the associations of inflammatory and endothelial dysfunction markers with long-term hypertension incidence in persons with type 1 diabetes mellitus. METHODS: The 15-year cumulative incidence of hypertension was measured in Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR) participants (n=795). Hypertension was defined by a systolic BP of ≥140 mmHg and/or a diastolic BP of ≥90 mmHg and/or history of current antihypertensive treatment. We measured serum high sensitivity C-reactive protein (hsCRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), soluble vascular cell adhesion molecule-1 (sVCAM-1), soluble intercellular adhesion molecule-1 (sICAM-1), and serum total homocysteine as “novel” markers of hypertension development. The relation of risk factors to hypertension incidence was determined using a proportional hazards approach with discrete linear logistic regression modeling. RESULTS: After controlling for age, gender, diabetes duration, body mass index, glycosylated hemoglobin, baseline systolic and diastolic blood pressure, proteinuria, and chronic kidney disease status, sVCAM-1 was significantly related to higher odds of developing incident hypertension (OR per log sVCAM-1 1.95; 95% CI 1.01–3.74). None of the other markers of inflammation and endothelial dysfunction were related to incident hypertension in the cohort. CONCLUSIONS: Our data showed that sVCAM-1 as a marker of endothelial dysfunction was the strongest predictor of hypertension risk in individuals with type 1 diabetes. This association was independent of the presence of diabetic nephropathy.